Analysis of a new best-practice advisory on time to initiation of antibiotics in surgical intensive care unit patients with septic shock. (February 2019) - Chanas, Tyler; Volles, David; Sawyer, Rob; Mallow-Corbett, Stephanie
Background: Early administration of antibiotics in septic shock is associated with decreased mortality. Promptly identifying sepsis and eliciting a response are necessary to reduce time to antibiotic administration. Methods: A best-practice advisory was introduced in the surgical intensive care unit to identify patients with septic shock and promote timely action. The best-practice advisory is triggered by blood culture orders and vasopressor administration within 24 h. The nurse or provider who triggers the alert may send an automatic notification to the intensive care unit resident, clinical pharmacist, and charge nurse, prompting bedside response and closer evaluation. Patients who met best-practice advisory criteria in the surgical intensive care unit from May 2016 through March 2017 were included. Outcomes included changes in antibiotics within 24 h, response to best-practice advisory, and time-to-antibiotics. Time-to-antibiotics was compared between a retrospective pre-intervention period and a six-month prospective post-intervention period defined by launch of the new best-practice advisory in September 2016. Data were analyzed by chi square, Mann–Whitney U, and Kruskal-Wallis. Results: During the first six months of best-practice advisory implementation, 191 alerts were triggered by 97 unique patients. Alert notification was transmitted in 79 best-practice advisories (41%), with pharmacist bedside response in 53 (67%). New antibiotics were started within 24 h following 83 best-practice advisories (43%). There was a trend toward decreased time-to-antibiotics following implementation of the best-practice advisory (7.4 vs. 4.2 h, p  = 0.057). Compared to the entire cohort, time-to-antibiotics was shorter when the team was notified and when a pharmacist responded to the bedside (4.2 vs. 1.6 vs. 1.2 hours). Conclusions: A new best-practice advisory has been effective at eliciting a rapid response and reducing the time-to-antibiotics in surgical intensive care unit patients with septic shock. Team notification and pharmacist response are associated with decreased time-to-antibiotics.